The Role of Glycogen Phosphorylase a Activation in in vivo Stimulation of Muscle Glycogenolysis - Leveille, Marcel Rheal (My University, 1978)
In animal models it has been demonstrated that stimulation of muscle glycogenolysis is associated with the activation of phosphorylase b (phos b) to phosphorylase a (phos a). In similar experiments in rat skeletal muscle, we found that sclatic nerve stimulation increased glycogenolysis in the first 15 sec. of stimulation in close correlation with an increase in the phos a activity. However by 30 sec. the phos a had returned to resting levels although glycogenolysis continued at a stimulated rate.
We did a series of experiments in human subjects to determine whether activation of phos b to phos a was essential in the activation of skeletal muscle glycogenolysis. Six normal male subjects underwent maximal voluntary isometric contraction of the quadriceps for 60 sec. Muscle needle biopsies were obtained at 0,10,20 and 60 sec. after onset of contraction. The rate of muscle glycogenolysis increased from less than 2.05 ± .35 at rest to 17.5 ± 0.7 umol/g during contraction, calculated from the increase in muscle lactate concentration. Enzyme analysis in the same biopsies revealed that the phos a: total phosphorylase ratios remained unchanged (0.05 ± 0.006). In separate experiments 5 normal male subjects exercised on a cycle ergometer at 66% of their VO₂ max. work load until exhaustion. After 40 min. exercise at 66% VO₂ max. load the muscle lactate concentration rose from 1.1 ± 0.005 umol/g at rest to 11.6 ± 0.8 umol/g. When subjects were exercised at 90% VO₂ max. until exhaustion; the change in muscle lactate was taken as a semi-quantitative reflection of the rate of muscle glycogenolysis. The change in the rate of music lactate production increased from 0.2 umol/g/min at the end of 66% work load, to 1.2 umol/g/min at exhaustion, indicating that glycogenolysis was stimulated. The phos a: total phosphorylase ratio and the active to total phosphorylase b kinase ratio remained unchanged at the end of 40 min. exercise and at exhaustion, from the resting value. We conclude that activation of phosphorylase (phos b to phos a conversion) is not an absolute prerequisite for stimulating glycogenolysis in skeletal muscle.
Keywords: Medical Sciences; Medical Sciences